Finite element analysis of the wrist arthroplasty in rheumatoid arthritis - Bajuri, M. N. (Springer Verlag, 2013)
This chapter presents information on finite element analyses (FEA) of stress distribution and contact pressure with the carpal articulation following total wrist arthroplasty (TWA) for rheumatoid arthritis (RA) of the wrist. Results from the previous analyses on the healthy and rheumatic wrist were used for comparison. A TWA model was developed based on parameters of a wrist implant named ReMotion™ total wrist system, and was then applied with the same boundary condition (static hand grip action) as the other two models. FEA has revealed that the contact pressure for the TWA model was five times lower than the RA model. Despite this encouraging finding, small variations in the amount of stress distribution were still present when compared to the healthy model. This comes to a conclusion that the used of TWA could reduces the high contact pressure induced in the RA model thus improving the diseased condition, however, there are rooms for improvement for TWA procedure to restore the biomechanical behaviour of the healthy wrist joint.